EEG Indices of Task Engagement - Kamzanova, A; Matthews, G; Kustubayeva, A (Farabi Journal of Social Sciences, 2016)
The aim of this study was to evaluate the sensitivity of a range of EEG indices to time-on-task effects and to a workloadmanipulation (cueing), during performance of a resource-limited vigilance task. Effects of task period and cueing on performance and subjective state response were consistent with previous vigilance studies and with resource theory.Two EEG indices – the Task Load Index (TLI) and global lower frequency (LF) alpha power – showed effects of task period and cueing similar to those seen with correct detections. Across four successive task periods, the TLI declined and LF alpha power increased. Cueing increased TLI and decreased LF alpha. Other indices – the Engagement Index (EI), frontal theta and upper frequency (UF) alpha failed to show these effects. However, EI and frontal theta were sensitive to interactive effects of task period and cueing, which may correspond to a stronger anxiety response to theuncued task